Improved Free Fatty Acid Production in Cyanobacteria with Synechococcus sp. PCC 7002 as Host - Ruffing, Anne M. (Frontiers in Bioengineering and Biotechnology, 2014)
Microbial free fatty acids (FFAs) have been proposed as a potential feedstock for renewable energy. The ability to directly convert carbon dioxide into FFAs makes cyanobacteria ideal hosts for renewable FFA production. Previous metabolic engineering efforts using the cyanobacterial hosts Synechocystis sp. PCC 6803 and Synechococcus elongatus PCC 7942 have demonstrated this direct conversion of carbon dioxide into FFAs; however, FFA yields in these hosts are limited by the negative impact of FFA production on the host cell physiology. This work investigates the use of Synechococcus sp. PCC 7002 as a cyanobacterial host for FFA production. In comparison to S. elongatus PCC 7942, Synechococcus sp. PCC 7002 strains produced and excreted FFAs at similar concentrations but without the detrimental effects on host physiology. The enhanced tolerance to FFA production with Synechococcus sp. PCC 7002 was found to be temperature-dependent, with physiological effects such as reduced photosynthetic yield and decreased photosynthetic pigments observed at higher temperatures. Additional genetic manipulations were targeted for increased FFA production, including thioesterases and ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO). Overexpression of non-native RuBisCO subunits (rbcLS) from a psbAI promoter resulted in more than a threefold increase in FFA production, with excreted FFA concentrations reaching >130 mg/L. This work illustrates the importance of host strain selection for cyanobacterial biofuel production and demonstrates that the FFA tolerance of Synechococcus sp. PCC 7002 can allow for high yields of excreted FFA.